Binding of NAD+-Glycohydrolase to Streptolysin O Stabilizes Both Toxins and Promotes Virulence of Group A Streptococcus - Jorge J. Velarde (American Society for Microbiology, 2017)
ABSTRACT The globally dominant, invasive M1T1 strain of group A Streptococcus (GAS) harbors polymorphisms in the promoter region of an operon that contains the genes encoding streptolysin O (SLO) and NAD+-glycohydrolase (NADase), resulting in high-level expression of these toxins. While both toxins have been shown experimentally to contribute to pathogenesis, many GAS isolates lack detectable NADase activity. DNA sequencing of such strains has revealed that reduced or absent enzymatic activity can be associated with a variety of point mutations in nga, the gene encoding NADase; a commonly observed polymorphism associated with near-complete abrogation of activity is a substitution of aspartic acid for glycine at position 330 (G330D). However, nga has not been observed to contain early termination codons or mutations that would result in a truncated protein, even when the gene product contains missense mutations that abrogate enzymatic activity. It has been suggested that NADase that lacks NAD-glycohydrolase activity retains an as-yet-unidentified inherent cytotoxicity to mammalian cells and thus is still a potent virulence factor. We now show that expression of NADase, either enzymatically active or inactive, augments SLO-mediated toxicity for keratinocytes. In culture supernatants, SLO and NADase are mutually interdependent for protein stability. We demonstrate that the two proteins interact in solution and that both the translocation domain and catalytic domain of NADase are required for maximal binding between the two toxins. We conclude that binding of NADase to SLO stabilizes both toxins, thereby enhancing GAS virulence. IMPORTANCE The global increase in invasive GAS infections in the 1980s was associated with the emergence of an M1T1 clone that harbors a 36-kb pathogenicity island, which codes for increased expression of toxins SLO and NADase. Polymorphisms in NADase that render it catalytically inactive can be detected in clinical isolates, including invasive strains. However, such isolates continue to produce full-length NADase. The rationale for this observation is not completely understood. This study characterizes the binding interaction between NADase and SLO and reports that the expression of each toxin is crucial for maximal expression and stability of the other. By this mechanism, the presence of both toxins increases toxicity to keratinocytes and is predicted to enhance GAS survival in the human host. These observations provide an explanation for conservation of full-length NADase expression even when it lacks enzymatic activity and suggest a critical role for binding of NADase to SLO in GAS pathogenesis.